2020
DOI: 10.1002/cam4.2801
|View full text |Cite
|
Sign up to set email alerts
|

Stromal score as a prognostic factor in primary gastric cancer and close association with tumor immune microenvironment

Abstract: Background Gastric cancer remains one of the major causes for tumor‐related deaths worldwide. Our study aimed to provide an understanding of primary gastric cancer and prompt its clinical diagnosis and treatment. Methods We integrated the expression profiles and overall survival information of primary gastric cancer in TCGA and GEO database and estimated the stromal score of each sample by the estimate R package. Stromal score and clinicopathologic characteristics assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
8
21
0
Order By: Relevance
“…In this study, we assessed the CC tumor stroma by assigning scores based on stromal signatures generated using the ESTIMATE algorithm ( 13 ), and found that patients with high stromal scores had worse survival prognosis than patients with low stromal scores. Our findings in CC are consistent with results for several other cancers, such as gastric cancer, prostate cancer, and early-stage non-small cell lung cancer ( 14 , 24 26 ). This indicates that the scores generated by this method may be a good tool to assess the CC tumor stroma condition and could be used as a prognosis factor for CC.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we assessed the CC tumor stroma by assigning scores based on stromal signatures generated using the ESTIMATE algorithm ( 13 ), and found that patients with high stromal scores had worse survival prognosis than patients with low stromal scores. Our findings in CC are consistent with results for several other cancers, such as gastric cancer, prostate cancer, and early-stage non-small cell lung cancer ( 14 , 24 26 ). This indicates that the scores generated by this method may be a good tool to assess the CC tumor stroma condition and could be used as a prognosis factor for CC.…”
Section: Discussionsupporting
confidence: 91%
“…More and more evidence revealed the tumor immune microenvironment is a crucial factor in tumor biology ( Mao et al, 2020 ). To interpret the role of PLAU expression in HNSCC based on immunity conception, the scores or proportions of tumor infiltrating cells were compared in TCGA-HNSCC cohort.…”
Section: Resultsmentioning
confidence: 99%
“…By analyzing specific gene expression, the algorithm infers the infiltration of stromal and immune cells and assesses tumor purity (18). Previous reports have applied the ESTIMATE to build prognostic models associated with TME in various malignancies, indicating the feasibility of the algorithm in the prediction of survival outcome (19)(20)(21). In the present study, we aimed to develop a Prognostic Microenvironment-related Immune Signature via ESTIMATE (PROMISE model) for glioma using expression profiles in The Cancer Genome Atlas (TCGA) and the Chinese Glioma Genome Atlas (CGGA) database.…”
Section: Introductionmentioning
confidence: 99%